IMPLEMENTASI PENGELOLAAN KEUANGAN PTM DALAM MENDUKUNG GOOD UNIVERSITY GOVERNANCE (GUG) PADA PERGURUAN TINGGI MUHAMMADIYAH DI SULAWESI SELATAN - Bintang, Asrijal; Haanurat, A Ifayani; Rustam, Andi (UNIVERSITAS MUHAMMADIYAH MAKASSAR, 2021)
The purpose of this study was to determine the implementation of financial management in PTM, the application of GUG in financial management in PTM, and the efforts of PTM in implementing GUG in accordance with the rules / guidelines for financial management of the Higher Education Council of PP Muhammadiyah. This research uses qualitative research. The research object used was the financial statements of Muhammadiyah Universities (PTM) in South Sulawesi with a sample size of 5 PTMs. The instrument used in this study was the interview with the informant, then the answers from the informants were analyzed and described descriptively. The results showed that Muhammadiyah Higher Education (PTM) in South Sulawesi had implemented a financial management system based on the management guidelines for the Muhammadiyah Higher Education Council, Muhammadiyah Higher Education (PTM) in South Sulawesi had implemented Goog University Governance principles, namely in terms of financial management. Regarding transparency and accountability, Muhammadiyah Higher Education (PTM) in South Sulawesi has made maximum efforts to apply the principles of Good University Governance which are adjusted to the financial management guidelines issued by the PP Muhammadiyah Dikti Council for Research and Development.Keywords: Financial Management, Good University Governance (GUG)